Neurocognitive effects related to COVID-19 (Research, Society and Development, 2022)
Introduction: The literature has shown increasing evidence of SARS-CoV-2 neurotropism and its ability to interact with neurons, glial cells and lymphocytes present in the Central Nervous System (CNS) leading to possible functional changes. Methodology: This article is a systematic literature review, descriptive and qualitative analysis that describes the direct relationship between COVID-19 and its impacts on the cognition of infected patients. Results And Discussion: A variety of neurological manifestations identified after SARS-CoV-2 infection were observed, which were described up to 6 months after the acute phase of infection. Regarding the affected area, although the pattern of neurocognitive symptoms is heterogeneous, there is a predominance of hypoactivity in the frontoparietal region and in the limbic circuit, fundamental structures in the cognitive aspects. Furthermore, these neurocognitive damages seem to be associated with the degree of impairment during acute infection, due to the decrease in oxygen supply to the CNS. Despite this, these cognitive changes are often cited as a direct consequence of immune hyperactivation, responsible for triggering an imbalance of neurochemical systems and neurotoxicity, in addition to the direct action of the virus on glial cells and neurons. Conclusion: We observed that there is a strong relationship between SARS-CoV-2 infection and neurocognitive changes in infected patients, with involvement of brain structures intrinsically involved in this function. Despite recent findings on the subject, further studies should be carried out to clarify the pathophysiology of these changes and propose therapeutic and preventive alternatives to improve the quality of life of these patients.